Quality of Life in Patients with Diffuse Lichen Planopilaris: A Cross-Sectional Study of 87 Moroccan Cases - Kelati, Awatef; Faik, Marwa; Chiheb, Soumiya; El Jazouli, Madiha; Jafferany, Mohammad (Dermatology Practical & Conceptual, 2026)
Introduction: Diffuse lichen planopilaris (DLPP) is a rare inflammatory scalp disorder that leads to progressive scarring alopecia, affecting patients' physical and psychological well-being.Objective: To assess quality of life (QoL) in Moroccan patients with DLPP and identify factors influencing their well-being.Materials and Methods: A cross-sectional study included 87 patients with DLPP at Cheikh Khalifa and Mohammed VI International University Hospitals in Casablanca, Morocco. The Dermatology Life Quality Index (DLQI) was used to assess the impact of DLPP on daily activities, emotional health, and social interactions.Results: The majority of patients were females (75.86%). Hair loss occurred in 90% of cases, with changes in hair quality (85.06%), pruritus (85.06%), and trichodynia (43.7%). Diffuse scales were visible in 87.36% of cases, with erythema present in 55.17%. Localized patches and early frontal fibrosing alopecia coexisted with DLPP in 6.9% and 65.52% of patients, respectively; 40.2% of patients had a DLQI >10, which indicates serious QoL impairment. The ‘symptoms’ domain was most affected, particularly among individuals with trichodynia (P=0.038) and changes in hair quality (P=0.009).Conclusion: DLPP markedly reduced QoL, especially in symptomatic forms. Trichodynia and decreased hair quality significantly impacted daily functioning and leisure activities. Early diagnosis and management are crucial to preserve hair potential and protect mental health.